EFFECT OF SUB-CHRONIC ORAL ADMINISTRATION OF HYDROMETHANOLIC STEM EXTRACT OF COSTUS AFER KER GAWL. (COSTACEAE) ON LIVER AND KIDNEY FUNCTIONS IN WISTAR RATS - Jimoh, A. A.; Maiha, B. B.; Chindo, B. A.; Ejiofor, J. I. (FUDMA JOURNAL OF SCIENCES, 2020)
The liver and the kidneys are two very important organs in the body and they are responsible for the metabolism and excretion of drugs respectively amongst several other functions. Severe adverse effects on these organs can lead to organ dysfunction or failure and a consequential effect on wellbeing and can even be life-threatening. This study investigated the effects of hydromethanolic stem extract of Costus afer Ker Gawl. (Costaceae) on liver and kidney function indices and the histopathology of the organs in Wistar rats. Serum liver enzymes which include: alanine amino transferase (ALT), aspartate amino transferase (AST) and alkaline phosphatase (ALP), total protein and albumin as well as serum urea, creatinine, sodium ions, potassium ions, chloride ions, bicarbonate ions were evaluated in biochemical studies. Sections of the liver and kidneys appropriately treated were examined microscopically for pathological lesions.There were decreased serum levels of ALT and ALP, but serum levels of AST increased at 500 and 1000 mg/kg doses. Serum levels of total protein (TP) and albumin concentration as well as urea and creatinine serum levels were not significantly (p>0.05) affected. However, histological examination of the liver and kidneys revealed slight to moderate hepatic necrosis and slight tubular necrosis respectively especially at 500 and 100 mg/kg doses of the extract. The results showed that the extract may be harmful to the liver and to a lesser extent the kidneys on prolonged administration and therefore it should be used with caution in such instances.
Keywords: Costus afer, kidney function, Liver function, Wistar rats